Determination of methods for achieving the surprise of the actions of the National Guard of Ukraine in a special operation for neutralizing illegal armed formations - Kolyanda, V. V.; Drobakha, G. А.; Adamchuk, М. М. (Honor and Law, 2019)
Based on the analysis of combat experience, methods have been developed for achieving the suddenness of the actions of the National Guard of Ukraine formations in a special operation on the neutralization of illegal armed formation, their ranking and identification of the most significant ones.